Markers of inflammation are negatively correlated with serum leptin in rheumatoid arthritis. Issue 8 (24th February 2005) - Popa, C; Netea, M G; Radstake, T R D S; van Riel, P L; Barrera, P; van der Meer, J W M
Abstract : Background: Leptin regulates food intake and modulates immunity and inflammation. A positive feedback mechanism has been described between tumour necrosis factor (TNF) and leptin, and it has been suggested that leptin potentiates inflammation in patients with rheumatoid arthritis (RA). Objective: To assess whether inflammation correlates with leptin concentrations in patients with RA, and whether anti-TNF treatment modulates leptin concentrations in these patients. Methods: Leptin, IL6 and CRP were measured (at baseline and after 2 weeks of treatment) in the blood of 31 patients with RA starting either anti-TNF treatment or placebo, and in 18 healthy controls. Results: In patients with RA, plasma leptin concentrations at baseline correlated inversely with the degree of inflammation as assessed by C reactive protein (CRP; r s 2  = 0.21, p<0.01) or interleukin (IL) 6 concentrations ( r s 2  = 0.22, p<0.008). Mean (SD) leptin concentrations did not differ between patients with RA and controls (6.0 (4.6) v 4.2 (2.8) ng/ml in men; 15.1 (7.9) v 13.4 (5.2) ng/ml in women). Short course anti-TNF treatment for 2 weeks did not modify leptin concentrations, despite significant reduction of CRP and IL6. Conclusion: A significant inverse correlation between inflammation and leptin concentrations was found in patients with active RA, although plasma leptin concentrations did not significantly differ from those in healthy controls. This suggests that active chronic inflammation may lower plasma leptin concentrations. Two weeks' treatment with anti-TNF did not change plasma leptin concentrations and longer treatment may be needed to see an effect on leptin.